Vibro-acoustic condition monitoring of Internal Combustion Engines: A critical review of existing techniques. (15th January 2018) - Delvecchio, S.; Bonfiglio, P.; Pompoli, F.
Highlights: Internal Combustion Engines → need of condition monitoring and diagnostic systems for (−) assessment of structural durability long-life cycles, (−) engine final status verification at the end of the assembly line, (−) maintenance costs reduction and consequent continuous monitoring of the ICE life during vehicle operations. Critical review of the state-of-the-art strategies and techniques based on vibro-acoustic signals that can monitor and diagnose malfunctions in Internal Combustion Engines (ICEs) under both test bench and vehicle operating conditions. Useful guideline for test engineers in understanding which types of fault can be diagnosed by using vibro-acoustic signals in sufficient time and which signal processing technique could be considered the most reliable and informative to be implemented for the fault in question. Abstract: This paper deals with the state-of-the-art strategies and techniques based on vibro-acoustic signals that can monitor and diagnose malfunctions in Internal Combustion Engines (ICEs) under both test bench and vehicle operating conditions. Over recent years, several authors have summarized what is known in critical reviews mainly focused on reciprocating machines in general or on specific signal processing techniques: no attempts to deal with IC engine condition monitoring have been made. This paper first gives a brief summary of the generation of sound and vibration in ICEs in order to place further discussion on fault vibro-acoustic diagnosis in context. An overview of the monitoring and diagnostic techniques described in literature using both vibration and acoustic signals is also provided. Different faulty conditions are described which affect combustion, mechanics and the aerodynamics of ICEs. The importance of measuring acoustic signals, as opposed to vibration signals, is due since the former seem to be more suitable for implementation on on-board monitoring systems in view of their non-intrusive behaviour, capability in simultaneously capturing signatures from several mechanical components and because of the possibility of detecting faults affecting airborne transmission paths. In view of the recent needs of the industry to (−) optimize component structural durability adopting long-life cycles, (−) verify the engine final status at the end of the assembly line and (−) reduce the maintenance costs monitoring the ICE life during vehicle operations, monitoring and diagnosing system requests are continuously growing up. The present review can be considered a useful guideline for test engineers in understanding which types of fault can be diagnosed by using vibro-acoustic signals in sufficient time in both test bench and operating conditions and which transducer and signal processing technique (of which the essential background theory is here reported) could be considered the most reliable and informative to be implemented for the fault in question.